Leveraging Next Generation Mobile Networks for Drone Telemetry and Payload Communication - Mombeshora, Ngonidzashe (Department of Electrical Engineering, 2024)
small Unmanned Aerial Systems (sUAS) have seen their adoption increasing over the past recent years. The adoption is by hobbyists for leisure or by the industry for business and commercial use and as such, use case applications may vary enormously. Such use cases include but are not limited to drone delivery, precision agriculture, search and rescue and surveillance. As the adoption continues to increase, so do the use cases and drone applications. However, drones have much more to offer, and their capabilities are not to be limited to the current possible applications. There is a plethora of drone applications that have not been made possible, mainly due to technological limitations. The main limitation to be addressed in this project pertains to communication. Drone use cases such as 8K video streaming, Augmented Reality and Virtual Reality (AR/VR), autonomous flights, and long-range surveillance requiring Beyond Visual Line of Sight (BVLOS) command and control are yet to be realized with efficiency for commercial viability. Limitations to be addressed in terms of communication include line of sight usage, data rates and latencies. This project investigates the use of mobile/cellular networks, specifically 5G (Fifth Generation) mobile networks, as a feasible option to address these limitations. Experiments will be done by creating a mobile network test-bed using open-source mobile network stacks such as OpenAirInterface and integrating that with current drone communication technologies such as MAVlink to realize a drone communication stack that utilizes mobile networks for communication. 4G Long Term Evolution (LTE), 5G Non-Standalone (NSA) and a 5G Standalone (SA) test-bed stack will be implemented, and flight tests will be carried out to draw out and assess the advantages and disadvantages that cellular networks bring forth. And how 5G can push forward the drone ecosystem towards more novel and unrealized use case applications. Whilst at the same time assessing the viability of these mobile network realisations in their current state and development roadmaps. It is to be noted that at the time of writing Open Source 5G testbeds are still quite early in their development phase, and hence might not perform according to the theoretical standards and expectations.